Analytical study of the acoustic field in a spherical resonator for single bubble sonoluminescence - Dellavale Clara, Hector Damian; Urteaga, Raul; Bonetto, Fabian Jose (Acoustical Society of America Institute of Physics, 2009)
Fil: Dellavale Clara, Hector Damian. Comision Nacional de Energia Atomica. Gerencia D/area de Energia Nuclear. Gerencia de Ingeniería Nuclear (cab). Laboratorio Cavitación y Biotecnología; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina